Adult Neurogenesis and Stroke: A Tale of Two Neurogenic Niches - Ceanga, Mihai; Dahab, Mahmoud; Witte, Otto W.; Keiner, Silke (Frontiers in Neuroscience, 2021)
In the aftermath of an acute stroke, numerous signaling cascades that reshape the brain both in the perilesional zone as well as in more distal regions are activated. Despite continuous improvement in the acute treatment of stroke and the sustained research efforts into the pathophysiology of stroke, we critically lag in our integrated understanding of the delayed and chronic responses to ischemic injury. As such, the beneficial or maladaptive effect of some stroke-induced cellular responses is unclear, restricting the advancement of therapeutic strategies to target long-term complications. A prominent delayed effect of stroke is the robust increase in adult neurogenesis, which raises hopes for a regenerative strategy to counter neurological deficits in stroke survivors. In the adult brain, two regions are known to generate new neurons from endogenous stem cells: the subventricular zone (SVZ) and the dentate subgranular zone (SGZ) of the hippocampus. While both niches respond with an increase in neurogenesis post-stroke, there are significant regional differences in the ensuing stages of survival, migration, and maturation, which may differently influence functional outcome. External interventions such as rehabilitative training add a further layer of complexity by independently modulating the process of adult neurogenesis. In this review we summarize the current knowledge regarding the effects of ischemic stroke on neurogenesis in the SVZ and in the SGZ, and the influence of exogenous stimuli such as motor activity or enriched environment. In addition, we discuss the contribution of SVZ or SGZ post-stroke neurogenesis to sensory, motor and cognitive recovery.